REVISION OF ALGAL FLORA (DIATOMS) CHECKLIST IN TIGRIS RIVER WITHIN BAGHDAD CITY -IRAQ - & et al., Al Hassany (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2021)
The present study was confined to a taxonomical and systematical revision of all so far, recorded diatoms from study was Tigris River within Baghdad district. There is a lot of confusion in the naming and nomenclature of this and other groups of algae in Iraq and even in the whole middle east. Since various systematic categories have been used and applied for the identification of diatoms and another algal taxon. More than half of all so far, known diatoms (a total of 345 taxa) have been renamed by the most recent internationally accepted system of classification. In the current study, Bacillariophyta in Tigris involves 27 species of Coscinodiscophyceae, 48 species of Fragilariophyceae whereas, all other 267 species were found within Bacillariophyceae within the Baghdad district. All these taxa have been rearranged, revised, and renamed accordingly, to avoid any confusion or mistakes in naming diatoms in the future, however undoubtedly this will enhance a wider revision to include all other known algal taxon in Iraq and even the whole Middle east.